(untitled) (Afrika und Übersee, 2021)
This paper contrasts the strategies for marking nominal and verbal plurality in the Mandara and Ɓata subgroups of Central Chadic, and offers some thoughts on their possible origin and development. The Mandara subgroup generally uses an /-a-/ infix for verbs, and the suffix /-ak/-ax/-ah/ for nouns. The Ɓata subgroup uses an /-ə-/ infix for both nouns and verbs, as well as a suffix /-j/ (or /-n/) for nouns. In both groups, the strategies used also depend upon the structure of the verb root. Data is provided for several languages, including little-documented languages such as Nzanyi, Bacama and Glavda. The data suggests that vowel infixes may originally have been used for both nominal and verbal plurals throughout Chadic, but the development of specific nominal plural suffixes gradually made the use of vowel infix plurals redundant in nouns. The nominal suffix /-ak/-ax/-ah/ would then have been a subsequent innovation in the verbal system for verb roots in the Mandara whose structure was incompatible with an infix strategy.